The choice of reference study period in building LCA – case-based analysis and arguments. Issue 3 (November 2020) - Rasmussen, F N; Zimmermann, R K; Kanafani, K; Andersen, C; Birgisdóttir, H
Abstract: Introduction: In building LCAs, the calculations are carried out over a chosen reference study period (RSP), which is commonly set around 50-60 years. When developing the Danish LCA method for DGNB certification, and later for the preparation of the voluntary sustainability class for the building code, longer RSP's were suggested by technical committees. Therefore, the RSP has been based on a technical approach to the lifetime of buildings, assuming 80 years for offices, 100 years for hospitals and 120 years for residential buildings. In this study, the effects and arguments of a shorter RSP are investigated. Method: LCA-based carbon profiles of 11 building cases were carried out to compare how the RSP influences the results. RSPs of 50, 80, 100 and 120 years were investigated. The building cases represent different use types, structural systems, material choices, on-site electricity generation and installation scope. Results: Results show no notable difference in ranking, the building cases in-between, at RSPs of 50 and 120 years. Further, the relationship between the best and the worst performing building stays around a three-fold difference, regardless of the RSP. Conclusion: The longer RSPs have serious drawbacks regarding the increasing uncertainties associated with the scenarios. Further, annualizing results of longer RSPs entail a fundamental ethical issue of effectively allocating environmental loads to future generations. These specific drawbacks of uncertainty and impacts distribution are reduced by using an RSP of 50 years. The RSP of 50 years thus represents a compromise between ensuring that impacts from replacements of shorter-lived building materials will be reflected in the results, and between encouraging that more emphasis can be put on the crucial material related emissions that affects the global carbon budgets here and now.